Consumers’ Attitude Toward Electric Vehicles in India : Mapping Psychological Antecedents and Consequences - Singh, Pushpinder; Sandhu, Inderpreet; Inder Singh, Amar (Indian Journal of Marketing, 2023)
Purpose : Deteriorating air quality, rising carbon footprint, and increasing fuel prices have called for India’s automobile industry to gear up for acute transformation. The current study, drawing parallel lines from SOR theory, investigated how the attitude toward EVs was affected by three psychological antecedents—utilitarian shopping value, conspicuous consumption, and lifestyle. Further, the study examined how this attitude impacted the intention of Indian consumers to purchase an EV and their ecological behavior. Design/Methodology/Approach : The study included 382 Indian consumers of EVs who constituted the sample population. A structured questionnaire was created to gather information from this sample. The SEM (structural equation modeling) approach was applied to draw conclusions from the data. Findings : The results indicated that out of three antecedents, only utilitarian shopping value had no significant relationship with attitude toward EVs. Also, the attitude was found to be positively related to purchase intention and ecological behavior. Implications : Manufacturers and marketers of EVs must include lifestyle and conspicuous aspects in their offerings. Moreover, they should work on enhancing the utilitarian value of EVs. Never should a person feel that he/she is paying more than he/she is getting. Special note for conspicuous consumers who are shedding huge resources to make a statement among peers. Originality Value : The current study was one of the prime ones to draw the impact of lifestyle, conspicuousness, and utilitarian values on attitudes toward EVs. Moreover, the current study provided a one-of-a-kind modified model of SOR theory by including unique stimuli and responses.